DESKRIPSI KECEMASAN MATEMATIS DAN DAMPAKNYA PADA KEMAMPUAN PEMAHAMAN KONSEP ALJABAR SISWA SMP NEGERI 11 BENGKULU TENGAH - Nurma Fitri Yanti; Fatrima Santri Syafri (Universitas Batanghari Jambi, 2026)
This study aims to describe the level of students' mathematics anxiety and analyze its impact on the ability to understand algebra concepts at SMP Negeri 11 Bengkulu Tengah. The research method used was descriptive qualitative with 25 seventh-grade students in the 2024/2025 academic year as research subjects. Research instruments included a mathematics anxiety questionnaire, algebra concept comprehension test, and semi-structured interviews. (1) The results showed that the majority of students (76%) experienced mathematics anxiety at moderate to high levels, with 40% of students in the high anxiety category, 36% in the moderate category, and 24% in the low category. (2) Students' ability to understand algebra concepts was also still low, with 48% of students in the poor and fair categories. Per-indicator analysis showed that students had the best mastery in restating concepts (82%), but were very weak in applying concepts to problem-solving (31.4%). (3) There was a consistent negative relationship between the level of mathematics anxiety and the ability to understand algebra concepts, where the higher the students' mathematics anxiety, the lower their ability to understand algebra concepts. Interview results with three research subjects showed that mathematics anxiety disrupted students' concentration, working memory, and self-confidence in doing mathematics, thus impacting the low achievement of algebra concept comprehension